Lomonosov Ridge off Greenland (LOMROG) 2007: Chemical and physical oceanography - Anderson, Leif (University of Gothenburg, 2019)
Conductivity Temperature Depth (CTD) and water sampling were carried out at 26 stations covering parts of the western Eurasian Basin and one station at the East Greenland continental margin. Water was collected using a 24-bottle rosette sampler equipped with 7.5 l Niskin type bottles and a CTD (Sea Bird 911+). When brought back onboard the rosette was moved into a heated double container as quickly as possible to avoid freezing the samples. Water samples were immediately drawn for the individual parameters to be determined in the following order: CFCs, oxygen, dissolved inorganic carbon/pH/total alkalinity, nutrients, oxygen-18, and salinity.

Konduktivitetstemperaturdjup (CTD) och vattenprovtagning utfördes vid 26 stationer som täckte delar av västra Eurasian Basin och en station vid kontinentalmarginalen i Östgrönland. Se engelska sidan för för detaljer.
Lomonosov Ridge off Greenland (LOMROG) 2007: Kemisk och fysisk oceanografi
Keywords: INORGANIC CARBON; CONDUCTIVITY; OCEAN TEMPERATURE; chemical oceanography; physical oceanography; Oceanographic geographical features; Geografiska oceanografiska förhållanden; Organic Chemistry; Organisk kemi; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Oceans; Kust och hav